Imaging anatomy. - Saremi, Farhood (Thieme, 2021)
"This atlas provides high-quality multiplanar and volumetric color-coded imaging techniques utilizing CT, MRI, or angiography, supplemented by cadaveric presentations and color drawings that best elucidate each specific anatomic region. Twenty-one chapters with concise text encompass thoracic wall, mediastinum, lung, vascular, and cardiac anatomy, providing readers with a virtual dissection experience. Many anatomical variants along with pathological examples are presented"--